La remuneración mínima vital y su impacto en los trabajadores - Bullard González, Alfredo (2014)
The diverse discussions around the Minimum Living Wage have been very controversial and constant over the past decades due to the economic, social and political context inwhich  Peru  was  immersed.  However, these discussions have reduced its recurrence overthe past years as a result of various factors, such as the development of labor rights andimprovement of the economic situation.However, it is extremely relevant to understand the importance of the role of the Minimum Living Wage and the implications it may have over the workers. That is why in the present exposition there will be a presentation  of the opposing positions regarding the impact–positive or negative– of the existence of a Minimum Living Wage on workers.